Public Compliance with the Ban on Busking in Banyumas Regency Based on Banyumas Regency Regional Regulation Number 14 of 2020 Concerning the Eradication of Community Diseases - Sapernong, Firlyanta (PT FORMOSA CENDEKIA GLOBAL, 2025)
The Banyumas Regency Government issued Banyumas Regency Regional Regulation No. 14 of 2020 concerning Amendments to Banyumas Regency Regional Regulation No. 16 of 2015 concerning the Prevention of Social Diseases. This regulation was issued with the intention of preventing the spread of social diseases such as beggars, buskers, vagrants, and abandoned children.. So the author is interested in studying the role of Satpol PP in preventing the spread of buskers in the Banyumas area. buskers in the Banyumas area. This research is of the normative juridical type, descriptive in nature, the main data is secondary data supplemented by supporting data in the form of interviews with, qualitative data analysis, and how to draw conclusions with deductive logic. Research results Buskers tend to obey the rules when Satpol PP conducts raids which causes a decrease in the number of buskers. The opportunity to commit acts and the lack of firmness of Satpol PP as supervisors and enforcers of the regional regulation make people return to busking, in addition to the cultural factors of society in the form of giving money to buskers also affect the level of community compliance to busk.